Finite-Time Control for 6-DOF Coupling On-Orbit Service Spacecraft With Pre-Defined Maximum Settling Time Guaranteed - Yufeng Gao; Chuanjiang Li; Dongyu Li (IEEE Access, 2021)
In this paper, for the precise relative motion control of the 6-DOF on-orbit service spacecraft, motivated by discovering a proper method to flexibly adjust the settling time before the control system design, a constraint function is proposed. Considering the ability of pre-defined performance techniques to pre-design response behaviors, a relevant control named by Pre-defined Maximum Settling Time Control (PMSTC) is investigated. Under the proposed framework, a PMSTC for spacecraft systems is designed with the aid of the power integrator-adding technique. The proposed controller allows us to design the response performance of a closed-loop system in advance, e.g., maximum settling time, maximum steady-state error, and maximum overshoot. More importantly, the PMSTC is able to separate the coupling of the settling time and the choosing of control parameters, which thus alleviate the complexity of the control design. The closed-loop system of the 6-DOF spacecraft showcases the full power of this approach, based on which, the rationality and effectiveness of the algorithm have been verified. To illustrate the characteristics of this algorithm, this paper compares the proposed algorithm with some state-of-the-art algorithms and analyzes the effect of parameters in detail.